Implementation of the Independent Curriculum in Building the Character Profile of Pancasila Students Based on Tri Hita Karana in Elementary Schools - Defa, Defa; Sutaja, I Made; Suja, I Wayan (Universitas Udayana, 2024)
One of the most important achievements of education is the development of Pancasila-based character and behavior that are able to make the name of the region and nation proud. Currently, education must be adapted to the current curriculum concept, namely the Merdeka curriculum, in order to produce students who are creative, imaginative, and characterful. Because Tri Hita Karana has a consistent goal of achieving happiness or harmony in life, it is very consistent with building a character profile of Pancasila students, which is one of the objectives of implementing the Independent Curriculum. Learning today is very close to technological changes; therefore, it is important to balance students in managing life harmony to build student character with the idea of Tri Hita Karana.